Laser Vaporization of Intracoronary Thrombus and Identifying Plaque Morphology in ST-Segment Elevation Myocardial Infarction as Assessed by Optical Coherence Tomography - Yuki Yamanaka; Yoshihisa Shimada; Daisuke Tonomura; Kazunori Terashita; Tatsuya Suzuki; Kentaro Yano; Satoshi Nishiura; Masataka Yoshida; Takao Tsuchida; Hitoshi Fukumoto (Journal of Interventional Cardiology)
Objectives. We evaluated the thrombus-vaporizing effect of excimer laser coronary angioplasty (ELCA) in patients with ST-segment elevation myocardial infarction (STEMI) by optical coherence tomography (OCT). Background. Larger intracoronary thrombus elevates the risk of interventional treatment and mortality in patients with STEMI. Methods. A total of 92 patients with STEMI who presented within 24 hours from the onset and underwent ELCA following manual aspiration thrombectomy (MT) were analyzed. Results. The mean baseline thrombolysis in myocardial infarction flow grade was 0.4 ± 0.6, which subsequently improved to 2.3 ± 0.7 after MT (p<0.0001) and 2.7 ± 0.5 after ELCA (p=0.0001). The median residual thrombus volume after MT was 65.7 mm3, which significantly reduced to 47.5 mm3 after ELCA (p<0.0001). Plaque rupture was identified by OCT in only 22 cases (23.9%) after MT, but was distinguishable in 36 additional cases after ELCA (total: 58 cases; 63.0%). Ruptured lesions contained a higher proportion of red thrombus than nonruptured lesions (75.9% vs. 43.3%, p=0.001). Significantly larger thrombus burden after MT (69.6 mm3 vs. 56.3 mm3, p<0.05) and greater thrombus reduction by ELCA (21.2 mm3 vs. 11.8 mm3, p<0.01) were observed in ruptured lesions than nonruptured lesions. Conclusions. ELCA effectively vaporized intracoronary thrombus in patients with STEMI even after MT. Lesions with plaque rupture contained larger thrombus burden that was frequently characterized by red thrombus and more effectively reduced by ELCA.